1990
DOI: 10.1677/joe.0.1270427
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones during development of a marsupial, the tammar wallaby, Macropus eugenii

Abstract: The levels of thyroid hormones in the plasma and the activities of 5'-deiodinase activity in liver and kidney were determined in the tammar wallaby, Macropus eugenii, from early pouch life to adulthood. The total concentration of plasma thyroxine (T4) was below 15 nmol/l before day 75 of pouch life, rose to about 75 nmol/l at day 160, and then decreased to about 12 nmol/l in the adult. The total concentration of plasma tri-iodothyronine (T3) was below 0.4 nmol/l before day 120, increased to 3 nmol/l by about d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…By day 200 full pelage has developed and the young leaves the pouch for the first time (See (40) for review). During this time, the young have elevated levels of TH in their blood: total T4 levels reach a peak around day 180, before declining to adult levels (16). Thyroidectomized pouch young showed retarded growth, fur development and homeothermy (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By day 200 full pelage has developed and the young leaves the pouch for the first time (See (40) for review). During this time, the young have elevated levels of TH in their blood: total T4 levels reach a peak around day 180, before declining to adult levels (16). Thyroidectomized pouch young showed retarded growth, fur development and homeothermy (40).…”
Section: Discussionmentioning
confidence: 99%
“…We suggested that this T4 distributor protein could serve as an additional THDP in the blood of the pouch young before its thyroid gland becomes functional, when the young obtains TH from the mother's milk. During this time, the young has elevated levels of THs in its blood (16). This raised the question as to whether W-TBP was the marsupial homologue of eutherian TBG.…”
mentioning
confidence: 99%
“…A method described by Janssens et al (1990) was used to define the plasma profile of GH in pouch young in terms of a simple exponential decline equation. The statistical package PRISM (GraphPad Software, San Diego, CA, USA) was used to fit the equation using a non-linear, least squares method.…”
Section: Statisticsmentioning
confidence: 99%
“…Thus, there is thyroidal involvement in normal growth of the tammar wallaby and turtles (429,828); in the control of food intake and energy usage in reptiles, birds, and fish (299,392,393,433,470); and in ovarian development and gestation in certain teleosts (497)(498)(499). These and other aspects of thyroidal endocrinology will be referred to again in later sections.…”
Section: Primary Structures Of Secretinmentioning
confidence: 99%